Role of Endovascular Aortic Repair in the Treatment of Infected Aortic Aneurysms Complicated by Aortoenteric or Aortobronchial Fistulae - Kan, Chung-Dann; Lee, Hsin-Ling; Yang, Yu-Jen (The Thoracic and Cardiovascular Surgeon, 2018)
Background The aim of this study was to compare outcomes and identify factors related to increased mortality of open surgical and endovascular aortic repair (EVAR) of primary mycotic aortic aneurysms complicated by aortoenteric fistula (AEF) or aortobronchial fistula (ABF).Methods Patients with primary mycotic aortic aneurysms complicated by an AEF or ABF treated by open surgery or endovascular repair between January 1993 and January 2014 were retrospectively reviewed. Outcomes were compared between the open surgery and endovascular groups, and a Cox's proportional hazard model was used to determine factors associated with mortality.Results A total of 29 patients included 14 received open surgery and 15 received endovascular repair. Positive initial bacterial blood culture results included Salmonella spp., oxacillin-resistant Staphylococcus aureus, and Klebsiella pneumoniae. Mortality within 1 month of surgery was higher in the open surgery than in the endovascular group (43 vs. 7%, respectively, p = 0.035). Shock, additional surgery to repair gastrointestinal (GI) or airway pathology, and aneurysm rupture were associated with a higher risk of death. Compared with patients without resection surgery, the adjusted hazard ratio of death within 4 years in patients with resection for GI/bronchial disease was 0.25. Survival within 6 months was better in the endovascular group (p = 0.016).Conclusion The results of this study showed that EVAR/thoracic EVAR (TEVAR) is feasible for the management of infected aortic aneurysms complicated by an AEF or ABF, and results in good short-term outcomes. However, EVAR/TEVAR did not benefit long-term survival compared with open surgery.
Keywords: aortic aneurysm; aortoenteric fistula; aortobronchial fistula; endovascular; EVAR; infection